2016
DOI: 10.1002/ece3.2315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate warming on plant autotoxicity in forest evolution: a case simulation analysis for Picea schrenkiana regeneration

Abstract: In order to explore how plant autotoxicity changes with climate warming, the autotoxicity of P. schrenkiana needles' water extract, organic extract fractions, and key allelochemical DHAP was systemically investigated at the temperature rising 2 and 4°C based on the data‐monitored soil temperature during the last decade in the stage of Schrenk spruce regeneration (seed germination and seedling growth). The results showed that the criterion day and night temperatures were 12°C and 4°C for seed germination, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…The dominant species of understory shrubs are Juniperus pseudosabina and Juniperus Sabina , and the main types of understory bryophytes consist of Dicranum scoparium and Hepnum revolutumare , while the herbs mainly include Stellaria songorica and Cortusa brother . In addition, the real-time monitoring of soil temperature with a total of sixty-nine sampling points from five field sites on the northern slops of the Tianshan Mountains showed that during natural seasons for P. schrenkiana regeneration from 2003 to 2012, the criterion day and night temperatures were 12 °C and 4 °C for seed germination, and 14 °C and 6 °C for seedling growth, respectively (Ruan et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant species of understory shrubs are Juniperus pseudosabina and Juniperus Sabina , and the main types of understory bryophytes consist of Dicranum scoparium and Hepnum revolutumare , while the herbs mainly include Stellaria songorica and Cortusa brother . In addition, the real-time monitoring of soil temperature with a total of sixty-nine sampling points from five field sites on the northern slops of the Tianshan Mountains showed that during natural seasons for P. schrenkiana regeneration from 2003 to 2012, the criterion day and night temperatures were 12 °C and 4 °C for seed germination, and 14 °C and 6 °C for seedling growth, respectively (Ruan et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, DHAP could act as a promoter at lower concentrations (0.1 mM) but an inhibitor at higher concentration (0.5 mM), and the concentration inflection point turning DHAP action direction would appear about 0.25 mM at 4/12 °C. This inflection point would shift to a lower level as environmental temperature increased, which would generate some crucial effects on the early regeneration process of P. schrenkiana in boreal forest (Ruan et al ., 2016). In spite that the real existence of plant autotoxic duality has been gradually recognized, its temperature dependence and ecological significance to forest evolution still need to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…is the native species in Middle Asia and the mountains of Asia, where usually it creates pure forests. This species is of the utmost importance in the mountain ecosystems, because it plays an important role in water and soil conservation, but the natural regeneration of P. schrenkiana has been problematic [145]. One of the possible reasons could be found in autotoxic secondary metabolites that are transferred to the soil with litter and root exudates and impede the growth of seedlings of P. schrenkiana .…”
Section: Allelochemicals In Treesmentioning
confidence: 99%
“…The phenomenon of allelopathy is defined as the process of plant-plant chemical interaction that results in either positive or negative effects (Donnelli et al 2008). Allelochemicals, which are regarded as secondary metabolites, are natural products delivered through decomposition, volatilization, leaching, and root exudation (Ruan et al 2016). They play an important role in the distribution of plant populations, the succession of communities, the nutrient chelation, and also in physiological processes (Wardle et al 2011, Vanderstukken et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Early stages of plant growth are expected to be more sensitive to climate change than adult stages and, as such, represent a main obstacle to recruitment (Donohue et al 2010). Seedling emergence is usually synchronized with seasonal changes in the environment (Ruan et al 2016). For the plasticity/adaptations of tree species, however, we know very little about their germination behavior in response to environmental changes (Berner et al 2013).…”
Section: Introductionmentioning
confidence: 99%